A Novel TTC19 Mutation in a Patient With Neurological, Psychological, and Gastrointestinal Impairment - Habibzadeh, Parham; Inaloo, Soroor; Silawi, Mohammad; Dastsooz, Hassan; Farazi Fard, Mohammad Ali; Sadeghipour, Forough; Faghihi, Zahra; Rezaeian, Mohaddeseh; Yavarian, Majid; Böhm, Johann; Faghihi, Mohammad Ali (Frontiers in Neurology, 2019)
Mitochondrial complex III deficiency, nuclear type 2 is an autosomal-recessive disorder caused by mutations in TTC19 gene. TTC19 is involved in the preservation of mitochondrial complex III, which is responsible for transfer of electrons from reduced coenzyme Q to cytochrome C and thus, contributes to the formation of electrochemical potential and subsequent ATP generation. Mutations in TTC19 have been found to be associated with a wide range of neurological and psychological manifestations. Herein, we report on a 15-year-old boy born from first-degree cousin parents, who initially presented with psychiatric symptoms. He subsequently developed progressive ataxia, spastic paraparesis with involvement of caudate bodies and lentiform nuclei with cerebellar atrophy. Eventually, the patient developed gastrointestinal involvement. Using whole-exome sequencing (WES), we identified a novel homozygous frameshift mutation in TTC19 gene in the patient (NM_017775.3, c.581delG: p.Arg194Asnfs*16). Advanced genetic sequencing technologies developed in recent years have not only facilitated identification of novel disease genes, but also allowed revelations about novel phenotypes associated with mutations in the genes already linked with other clinical features. Our findings expanded the clinical features of TTC19 mutation to potentially include gastrointestinal involvement. Further functional studies are needed to elucidate the underlying pathophysiological mechanisms.